Experimental results of electromagnetic analysis on smartcard - Quy, Tran Ngọc; Quyen, Phung Van (Journal of Science and Technology on Information security, 2023)
Abstract— Electromagnetic analysis attack is a form of side channel attack that can be used to reveal secret information of a cryptographic device by examination of electromagnetic radiations. The effectiveness of EMA has a large dependences on the quality of the electromagnetic radiation measured by the measuring system and how the EM traces are simulated during the key recovery procedures. In this paper, we propose the practical procedure for electromagnetic analysis attack methods and the experimental results of EMA on smartcard that implemented AES algorithm, including assessing the influence of measuring system, radiation leakage model on effectiveness of attacks.